The parasitic barnacle Peltogaster reticulata Shiino, 1943 (Rhizocephala,Peltogastridae) from Russian waters of the Sea of Japan: morphological description, molecular identification and complete larval development - Korn, Olga M.; Golubinskaya, Darya D.; Sharina, Svetlana N. (Zootaxa, 2020)
A rhizocephalan parasite of the hermit crab Pagurus minutus Hess, 1865 (Decapoda, Paguridae) is described from Russian waters using morphological and molecular methods. Partial sequences of the mitochondrial cytochrome c oxidase subunit I gene (COI) were used as a genetic marker. We refer this species to Peltogaster reticulata Shiino, 1943 (Rhizocephala, Peltogastridae) based on its morphological description, since genetic data for the species from its type locality are lacking. The species can be distinguished from its known congeners by the reticular pattern of the external cuticle. Peltogaster reticulata is the sister taxon to P. postica Yoshida & Osawa, 2011 (in Yoshida et al. 2011), inhabiting the same host in southwestern Japan. The complete larval development of Peltogaster reticulata, including five naupliar and one cypris stage, is described and illustrated using SEM.